Paleointensity of the geomagnetic field in the Late Cretaceous and earliest Paleogene obtained from drill cores of the Louisville seamount trail - Toshitsugu Yamazaki; Yuhji Yamamoto (Geochemistry, Geophysics, Geosystems)
Abstract Information on the strength of the geomagnetic field is important for understanding the behavior of the geodynamo. Polarity reversal frequency increases toward the late Cenozoic since the end of the Cretaceous Normal Superchron. Accumulating reliable paleointensity data in this time interval is still desired for elucidating the possibility of a link between reversal frequency and paleointensity. We conducted a paleointensity study on 288 samples from four seamounts from ∼74 to ∼50 Ma in age that constitutes the Louisville seamount trail. Based on thermomagnetic curves and scanning electron microscopy, we first excluded 134 samples that showed evidence for low‐temperature oxidation. We then applied the Tsunakawa‐Shaw method with low‐temperature demagnetization and double heating after rejecting some samples that do not preserve stable primary remanence, and 52 successful results were obtained. An average virtual axial dipole moment (VADM) of 3.75 ± 1.52 (1022 Am2) was obtained at Site U1372 on Canopus seamount (∼74 Ma) based on 16 independent measurements. Sites U1373 and U1374 on Rigil seamount (∼70 Ma) yielded a mean of 3.79 ± 1.40 (n = 16), and Site U1376 on Burton seamount (∼65 Ma) yielded a mean of 3.70 ± 1.37 (n = 8). These VADMs are similar to the long‐term average of the last 200 Myr by Tauxe et al. (2013) and the mean of the last 5 Myr by Yamamoto and Tsunakawa (2005). The volcanic sequence drilled at Site U1372 probably belongs to Chron C33n of 5.59 Myr long, whereas others belong to shorter chrons. Our results support no discernible relationship between polarity length and paleointensity.